Response of broiler chickens to different levels of calcium, non-phytate phosphorus and phytase. Issue 6 (1st November 2016) - Akter, M.; Graham, H.; Iji, P. A.
ABSTRACT: 1. Five hundred and seventy six-d old Ross 308 broiler chicks (6 cages per diet, 8 birds per cage in 3 × 2 × 2 factorial arrangement) were fed on maize–soybean meal-based diets containing three concentrations of Ca (6, 8 or 10 g/kg), two concentrations of non-phytate phosphorus (NPP) (3 or 4 g/kg) and two levels of exogenous microbial phytase (0 or 500 FTU/kg) from d 0 to 35. 2. Body weight (BW), feed intake (FI) and mortality records were collected. Two birds per replicate were killed at 24 d of age to obtain tibia samples. 3. Increasing Ca level significantly reduced the FI and body weight gain (BWG) between hatch and 10 and 24 d, especially with the phytase-supplemented diets. However, phytase supplementation of the diet containing 4 g NPP/kg improved the FI and BWG at d 10 and 24. At d 24, phytase supplementation improved feed conversion ratio (FCR) of birds that consumed diets containing high NPP. The overall FCR was better in birds offered the phytase-supplemented, medium-Ca diet. 4. There was a significant reduction in length, width and breaking strength of the tibia bone in birds fed on a diet with high Ca and low NPP. Phytase supplementation improved the tibia ash content and bone breaking strength of chicks fed on the diet containing 8 and 4 g/kg Ca and NPP, respectively. The Ca content of the tibia bone was low in birds fed on diets with 6 and 4 g/kg Ca and NPP, respectively, but this was counteracted by phytase supplementation. 5. Birds fed on diets with 4 g/kg NPP had the best carcass percentage and parts yield. Phytase supplementation to high-Ca diets significantly reduced the carcass yield of birds. 6. These results confirmed the detrimental effect of high dietary Ca on phytase activity and subsequent growth and bone development of birds, especially when NPP is in short supply.